Ответы и объяснения

gostrevan
yarovoe
гюйс
yarovoe

1.(1/4)¹/²·16¹/²-2⁻¹·(1/25)⁻¹/²·8¹/³=(16/4)¹/²-0,5·25¹/²·∛8=
=√4-0,5·√25∛8=2-0,5·5·2=2-5=-3

3.(1-a⁻¹/²)/(1+a¹/²)-(a¹/²+a⁻¹/²)/(a-1)=
(1-a⁻¹/²)·(a-1)- (1+a¹/²)·(a¹/²+a⁻¹/²)/(1+a¹/²)(a-1)=
(a-a¹/²-1+a⁻¹/²-a¹/²-a⁻¹/²-a-1)/ (1+a¹/²)(a-1)=-2(a¹/²+1)/ (1+a¹/²)(a-1)=
=-2/(a-1)=2/(1-a)

5.0
1 оценка
1 оценка
Оцени!
Оцени!
Лучший Ответ!
гюйс

( \frac{1}{4} )^{ \frac{1}{2} }*16^{ \frac{1}{2} }-2^{-1} ( \frac{1}{25})^{- \frac{1}{2}}*8 ^{ \frac{1}{3} }=(2^{-2} )^{ \frac{1}{2}}*(2^{4} )^{ \frac{1}{2}}-2^{- 1 } *(5^{-2})^{- \frac{1}{2} }*(2^{3})^{ \frac{1}{3} }           =2^{-1}*2^{2} -2^{-1}*2*5=2-5= - 3

.
 \frac{1-a^{- \frac{1}{2} } }{1+a^{ \frac{1}{2} } } -  \frac{a^{ \frac{1}{2} }+a^{ \frac{1}{2} }  }{a-1}= \frac{(1-a^{- \frac{1}{2} })(a-1)-(a^{ \frac{1}{2} }+a ^{ \frac{1}{2} })(1+a ^{ \frac{1}{2} })  }{(1+a^{ \frac{1}{2} })(a-1)}=   \frac{a-1-a^{ \frac{1}{2} }+a^{ -\frac{1}{2} } - a^{- \frac{1}{2} }-a-a^{ \frac{1}{2} }-a}{a-1+a-a^{ \frac{1}{2} } } = \frac{-1-a-2a^{ \frac{1}{2} } }{-1-a^{ \frac{1}{2} } } = \frac{1+a+a^{ \frac{1}{2} } }{1+a^{ \frac{1}{2} } }

5.0
2 оценки
2 оценки
Оцени!
Оцени!